Unilateral reduction of medium-term carbon emissions via taxing emissions and consumption - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2011)
Internalizing the global negative externality of carbon emissions requires flattening the extraction path of non-renewable fossil-fuel resources (= world carbon emissions). Following Eichner and Pethig (2011b) we set up a two-country two-period model in which one of the countries represents a sub-global climate coalition that implements a binding ceiling on the world's first-period emissions. The other country is the rest of the world and refrains from taking action. The climate coalition has at its disposal sign-unconstrained taxes on emissions in both periods, as in Eichner and Pethig (2011b), but in the present study it has the additional option of taxing consumption. The central question is whether and how the coalition makes use of consumption taxes along with emission taxes in its unilateral cost-effective ceiling policy. We identify cost-effective policies under various conditions and find that all consist of a (positive) tax on first-period consumption and of emission taxes whose rates are negative in the second period but may take on either sign in the first period.
Keywords: H21; H23; Q54; Q58; 330; carbon emissions; ceiling; unilateral; cost-effective regulation; Kohlendioxid; Luftverunreinigung; Klimaschutz; Ökosteuer; Verbrauchsteuer; Steuerwirkung; Zwei-Länder-Modell; Theorie